2020
DOI: 10.1177/0036850420980617
|View full text |Cite
|
Sign up to set email alerts
|

Design and topology optimization of air conditioning suspension bracket for metro

Abstract: During the operation of subway vehicles, the vibration of air conditioning units is mainly transmitted to the vehicle body through the suspension support, which seriously affects the stability and comfort of the vehicle during operation. Therefore, the design and optimization of the suspension support of air conditioning units has become a hot topic in the research of the dynamic characteristics of subway vehicles. In this paper, the rigid and flexible coupling dynamic model of metro is firstly calculated to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Studies have shown that every 10% reduction in vehicle mass, fuel consumption can be reduced by 6%–8%, and exhaust emissions will be reduced by 5%–6%, which achieves the effect of energy saving and emission reduction and promotes the development of automobile lightweight to some extent. 1 At present, the main ways to achieve lightweight usually include structural optimization, 2–9 new materials, 10 and new processes. 11 Among them, Liang et al 2 optimized the structure of a gearbox under multiple load conditions, and the results showed that the mass of optimized gearbox was reduced by 7.6% compared with the initial model, the strength and stiffness were not weakened, and the first and second-order natural frequencies increased about 4.1% and 5.0%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that every 10% reduction in vehicle mass, fuel consumption can be reduced by 6%–8%, and exhaust emissions will be reduced by 5%–6%, which achieves the effect of energy saving and emission reduction and promotes the development of automobile lightweight to some extent. 1 At present, the main ways to achieve lightweight usually include structural optimization, 2–9 new materials, 10 and new processes. 11 Among them, Liang et al 2 optimized the structure of a gearbox under multiple load conditions, and the results showed that the mass of optimized gearbox was reduced by 7.6% compared with the initial model, the strength and stiffness were not weakened, and the first and second-order natural frequencies increased about 4.1% and 5.0%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, there has been in-depth research on the optimization method of structural parts [5]. e authors in [6][7][8][9][10][11] separately optimized the structure of energy-absorbing structure, carbody structure, and the subway vehicle air-conditioning suspension.…”
Section: Introductionmentioning
confidence: 99%